Scientific awareness of marine accidents in Europe: A bibliometric and correspondence analysis - Demirci, S. M. Esad; Elcicek, Huseyin (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
Marine accidents are a significant issue that can lead to loss of life, damage to ships and cargo, and harm to the marine environment. To gain better understanding of scientific awareness of marine accidents occurred in European countries, this study conducted a bibliometric and correspondence analysis of the scientific literature. Bibliometric analysis was employed to examine various publications, which were released during the period between 2012 and December 2022. Moreover, correspondence analysis was used to classify and analyze marine accidents based on the severity and the consequence of the accidents. The findings indicate that scientific awareness of researchers in countries where serious and very serious marine accidents occur is also high. However, Norway stands out as the country with the highest scientific awareness of researchers despite experiencing marine accidents with less serious. The most significant factor contributing to the prominence of researchers here is their collaborations with researchers from other countries. Overall, this study sheds light on the need for further research and action to improve marine accident prevention. Collaborative efforts involving researchers, maritime stakeholders, and policymakers are necessary to address the complex challenges of marine accidents and to ensure the maritime safety and protection of the marine environment.
Keywords: Maritime safety; Marine accident; European countries; Bibliometric analysis; Correspondence analysis; MARITIME TRANSPORTATION SYSTEMS; RISK ANALYSIS; COLLISION; SAFETY; FRAMEWORK; LIGHT; LIFE; Engineering; Public, Environmental & Occupational Health; Social Sciences - Other Topics; Transportation